Agroecological transitions reveal trade-offs and synergies among ecosystem services - Mathieu Delandmeter; Bruno Basso; Jérôme Bindelle; Benjamin Dumont (Science of The Total Environment, 2026)

Livestock Integration Into Cropping Systems Enhances Their Climate Change Resistance and Mitigation While Reducing Their Environmental Impacts - Mathieu Delandmeter; Bruno Basso; Xavier Fettweis; Christophe Lacroix; Pierre Aubry; Jérôme Bindelle; Benjamin Dumont (Global Change Biology, 2026)
The sustainability of cropping systems is linked to their circularity, which is their ability to close resource cycles such as carbon and nitrogen through strategies for managing crop residues, byproducts, and other inputs. Here, we investigate three crop rotations—business‐as‐usual (BAU), vegan, and integrated crop‐livestock systems (ICLS)—varying in livestock integration, crop residue fate, and human diet sustained. Under ten climate change scenarios, we compare their impacts on multiple ecosystem services during 24 years over 541,800 ha in Belgium using a validated crop model. All three circularity scenarios are found to be net greenhouse gas (GHG) emitters, with increasing intensity under climate change. The BAU system, favoring cash crops such as sugarbeet or potato, demonstrates the highest productivity, which, however, is highly variable across years and comes with greater environmental impacts such as GHG emissions (+45% and +23% compared to ICLS and Vegan in average—i.e., across all sites and climate scenarios). The Vegan system has lower carbon sequestration than the ICLS due to the lack of pasture and livestock, which, however, is partly offset by the regular incorporation of crop residues into the soil. Finally, ICLS, which include temporary pastures and sheep, demonstrate intermediate productivity levels compared to the other systems. However, they offer the greatest stability and resistance to extreme weather (+43% and +86% for stability compared to BAU and Vegan, in average), with better environmental performance. Therefore, our study reveals the benefits of crop‐livestock systems in terms of climate change adaptation, through stability and resistance to extreme climate events, and mitigation, through soil carbon sequestration and reduced greenhouse gas emissions and nitrate leaching. Moreover, our findings highlight the critical links between farm‐level circularity, soil‐crop feedbacks, human diet, and climate change.

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Bridging dimensions: a comparative analysis of 2D and 3D in vitro models for hepatocellular carcinoma research - Leticia C. Valente; Luana Riechelman-Casarin; Laura L. P. Esteves; Gabriel P. Bacil; Tereza Cristina da Silva; Mathieu Vinken; Bruno Cogliati; Scott L. Friedman; Amedeo Columbano; Luís Fernando Barbisan; Guilherme R. Romualdo (Archives of Toxicology, 2025)

Understanding the relationship between foraminiferal Mg/Ca and clumped isotope thermometers - Marion Peral; Thibaut Caley; Bruno Malaizé; Thomas Extier; Linda Rossignol; Héloïse Barathieu; Émilie Dassié; Franck Bassinot; Dominique Blamart; Mathieu Daëron (Geochimica et Cosmochimica Acta, 2025)

Use of commercial serological tests to detect schistosomiasis in sheep - Manon Blin; Félix Bornier; Nathalie Lazzarin; Justine Alonzi; Bruno Polack; Isabelle Vallée; Anne Rognon; Eglantine Mathieu-Bégné; Myriam Thomas; Denis Limonne; Jérôme Boissier (Veterinary Parasitology, 2025)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Deciphering microbial communities of three Savoyard raw milk cheeses along ripening and regarding the cheese process - Cresciense Lecaudé; Nicolas Orieux; Sarah Chuzeville; Alicia Bertry; Eric Coissac; Frederic Boyer; Aurélie Bonin; Nelly Colomb-Boeckler; Bruno Mathieu; Manon Recour; Joël Vindret; Céline Pignol; et al. (International Journal of Food Microbiology, 2024)

Telocytes: current methods of research, challenges and future perspectives - Bruno D. A. Sanches; Francisco B. S. Teófilo; Mathieu Y. Brunet; Victor M. Villapun; Kenny Man; Lara C. Rocha; Jurandyr Pimentel Neto; Marta R. Matsumoto; Juliana S. Maldarine; Adriano P. Ciena; Sophie C. Cox; Hernandes F. Carvalho (Cell and Tissue Research, 2024)

Two new flavone glycosides from the leaves of Ochna afzelii Oliv. (Ochnaceae) - Morel Hervé D. Kakabi; James D. Simo Mpetga; Jean-De-Dieu Tamokou; Germaine Takongmo Matsuete; Romeo Désiré T. Nago; Gabin Thierry M. Bitchagno; Bruno N. Lenta; Norbert Sewald; Mathieu Tene; Augustin Silvère Ngouela (Natural Product Research, 2024)

Global patterns and environmental drivers of forest functional composition - Elise Bouchard; Eric B. Searle; Pierre Drapeau; Jingjing Liang; Javier G. P. Gamarra; Meinrad Abegg; Giorgio Alberti; Angelica Almeyda Zambrano; Esteban Alvarez‐Davila; Luciana F. Alves; Valerio Avitabile; Gerardo Aymard; et al. (Global Ecology and Biogeography, 2024)
Aim To determine the relationships between the functional trait composition of forest communities and environmental gradients across scales and biomes and the role of species relative abundances in these relationships. Location Global. Time period Recent. Major taxa studied Trees. Methods We integrated species abundance records from worldwide forest inventories and associated functional traits (wood density, specific leaf area and seed mass) to obtain a data set of 99,953 to 149,285 plots (depending on the trait) spanning all forested continents. We computed community‐weighted and unweighted means of trait values for each plot and related them to three broad environmental gradients and their interactions (energy availability, precipitation and soil properties) at two scales (global and biomes). Results Our models explained up to 60% of the variance in trait distribution. At global scale, the energy gradient had the strongest influence on traits. However, within‐biome models revealed different relationships among biomes. Notably, the functional composition of tropical forests was more influenced by precipitation and soil properties than energy availability, whereas temperate forests showed the opposite pattern. Depending on the trait studied, response to gradients was more variable and proportionally weaker in boreal forests. Community unweighted means were better predicted than weighted means for almost all models. Main conclusions Worldwide, trees require a large amount of energy (following latitude) to produce dense wood and seeds, while leaves with large surface to weight ratios are concentrated in temperate forests. However, patterns of functional composition within‐biome differ from global patterns due to biome specificities such as the presence of conifers or unique combinations of climatic and soil properties. We recommend assessing the sensitivity of tree functional traits to environmental changes in their geographic context. Furthermore, at a given site, the distribution of tree functional traits appears to be driven more by species presence than species abundance.

The DeepFaune initiative: a collaborative effort towards the automatic identification of European fauna in camera trap images - Noa Rigoudy; Gaspard Dussert; Abdelbaki Benyoub; Aurélien Besnard; Carole Birck; Jérome Boyer; Yoann Bollet; Yoann Bunz; Gérard Caussimont; Elias Chetouane; Jules Chiffard Carriburu; Pierre Cornette; et al. (European Journal of Wildlife Research, 2023)

Persistent headaches one year after bacterial meningitis: prevalence, determinants and impact on quality of life - Rémi Nguyen Van; Sarah Tubiana; Thomas De Broucker; Joseph Cédric; Carine Roy; Marie-Caroline Meyohas; Thierry Prazuck; Catherine Chirouze; Bruno Hoen; Xavier Duval; Matthieu Revest; Bruno Mourvillier; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Deep behavioral impairment in the pearl oyster Pinctada radiata exposed to anthropogenic noise and light stress - Mohcine Charifi; Razan Khalifa; Bruno W. Giraldes; Mohamedou Sow; Zainab Hizam; Mathieu Carrara; Eric Maneux; Shafeeq Hamza; Anne Bassères; Philippe Blanc; Alexandra Leitão; Jean-Charles Massabuau (Frontiers in Marine Science, 2023)
The pearl oyster Pinctada radiata is an iconic species in the Arabian Gulf, which is one of the ecosystems most at risk in the world because of the multiple sources of pollution it faces. Alongside chemical pollution, the Gulf is ranked first with regard to noise and light pollution, and pearl oyster populations are at risk. The impact of these latter types of pollution on marine invertebrates is still poorly known. We used the difference in noise and brightness that can exist between a very quiet room without artificial lighting and a standard laboratory room equipped with a standard aquarium as a testbed to explore the possible impact of noise and light pollution on the behavioral and biological traits of Pinctada radiata without added chemical exposure. During an experiment that lasted 2.5 months, we analyzed their grouping behavior, valve activity, biological rhythm, growth rate and spawning activity. In the standard aquarium kept in the laboratory room, the oysters dispersed instead of regrouping as in their natural environment, regrouping which was observed in the quiet room. They stayed closed longer, the opening amplitude of their valves was systematically lower, and in the closed position, they squeezed their valves more tightly when subjected to noise and light pollution. Their daily opening rhythm was strongly structured by switching the electric light on and off, and females showed significantly less egg-laying behavior. In conclusion, seemingly innocuous human activities can lead to very significant alterations in pearl oyster behavior. We propose that it could have significant effects on populations and ecosystems.

The environment: A vector of phenotypic disparity during the settlement phase of coral reef fishes - Mathieu Reynaud; Emma Gairin; David Lecchini; Vincent Laudet; Bruno Frédérich (Journal of Experimental Marine Biology and Ecology, 2023)

Effects of glyphosate exposure on western diet-induced non-alcoholic fatty liver disease in mice - Guilherme R. Romualdo; Letícia Cardoso Valente; Ana Carolina Sprocatti dos Santos; Núbia Alves Grandini; Camila Renata Correa Camacho; Mathieu Vinken; Bruno Cogliati; De-Xing Hou; Luís Fernando Barbisan (Environmental Toxicology and Pharmacology, 2023)

Evaluation of functional candidate biomarkers of non-genotoxic hepatocarcinogenicity in human liver spheroid co-cultures - Bruna dos Santos Rodrigues; Kaat Leroy; Milos Mihajlovic; Sybren De Boever; Sarah Vanbellingen; Bruno Cogliati; Joeri L. Aerts; Mathieu Vinken (Archives of Toxicology, 2023)

Exposure to polyethylene microplastics alters immature gut microbiome in an infant in vitro gut model - Elora Fournier; Jeremy Ratel; Sylvain Denis; Mathilde Leveque; Philippe Ruiz; Carine Mazal; Frederic Amiard; Mathieu Edely; Valerie Bezirard; Eric Gaultier; Bruno Lamas; Eric Houdeau; et al. (Journal of Hazardous Materials, 2023)

Microplastics: What happens in the human digestive tract? First evidences in adults using in vitro gut models - Elora Fournier; Mathilde Leveque; Philippe Ruiz; Jeremy Ratel; Claude Durif; Sandrine Chalancon; Frederic Amiard; Mathieu Edely; Valerie Bezirard; Eric Gaultier; Bruno Lamas; Eric Houdeau; et al. (Journal of Hazardous Materials, 2023)

Persistent organochlorine pesticides in periprostatic adipose tissue from men with prostate cancer: Ethno-geographic variations, association with disease aggressiveness - Jean-Philippe Antignac; Sandy Figiel; Michèle Pinault; Pascal Blanchet; Franck Bruyère; Romain Mathieu; Souhil Lebdai; Georges Fournier; Jerome Rigaud; Karine Mahéo; Philippe Marchand; Ingrid Guiffard; et al. (Environmental Research, 2023)

Alkenylbenzoquinones and other compounds from the fruit of Maesa lanceolata exhibited potent cytotoxic, antibacterial, and antiradical scavenging activities § - Amanda Seumo Seumo; Arno Rusel D. Nanfack; Blanche Laure Ndontsa; Gabin Thierry M. Bitchagno; Roukayatou Mbouangouere; Bruno N. Lenta; Norbert Sewald; Pierre Tane; Mathieu Tene; Silvère Augustin Ngouela (Natural Product Research, 2022)

Two new triterpenoid fatty acid esters from Schefflera barteri Harms (Araliaceae) § - Judith Flore T. Mbougnia; Gabin Thierry M. Bitchagno; Steven Collins N. Wouamba; Jean-Bosco Jouda; Maurice Ducret Awouafack; Mathieu Tene; Bruno Ndjakou Lenta; Simeon Fogue Kouam; Pierre Tane; Norbert Sewald (Natural Product Research, 2022)

Preconception maternal cocaine self-administration increases the reinforcing efficacy of cocaine in male offspring - Bruno Fant; Mathieu E. Wimmer; Sarah E. Swinford-Jackson; John Maurer; Duncan Van Nest; R. Christopher Pierce (Psychopharmacology, 2019)

From Observation to Information and Users: The Copernicus Marine Service Perspective - Pierre Yves Le Traon; Antonio Reppucci; Enrique Alvarez Fanjul; Lotfi Aouf; Arno Behrens; Maria Belmonte; Abderrahim Bentamy; Laurent Bertino; Vittorio Ernesto Brando; Matilde Brandt Kreiner; Mounir Benkiran; Thierry Carval; et al. (Frontiers in Marine Science, 2019)

Contamination of soils by metals and organic micropollutants: case study of the Parisian conurbation - Johnny Gaspéri; Sophie Ayrault; Elodie Moreau-Guigon; Fabrice Alliot; Pierre Labadie; Hélène Budzinski; Martine Blanchard; Bogdan Muresan; Emilie Caupos; Mathieu Cladière; David Gateuille; Bruno Tassin; et al. (Environmental Science and Pollution Research, 2018)

Genetic ablation of pannexin1 counteracts liver fibrosis in a chemical, but not in a surgical mouse model - Sara Crespo Yanguas; Tereza C. da Silva; Isabel V. A. Pereira; Michaël Maes; Joost Willebrords; Valery I. Shestopalov; Bruna M. Goes; Marina Sayuri Nogueira; Inar Alves de Castro; Guilherme R. Romualdo; Luís F. Barbisan; Eva Gijbels; et al. (Archives of Toxicology, 2018)

Soil parent material—A major driver of plant nutrient limitations in terrestrial ecosystems - Laurent Augusto; David L. Achat; Mathieu Jonard; David Vidal; Bruno Ringeval (Global Change Biology, 2017)
Because the capability of terrestrial ecosystems to fix carbon is constrained by nutrient availability, understanding how nutrients limit plant growth is a key contemporary question. However, what drives nutrient limitations at global scale remains to be clarified. Using global data on plant growth, plant nutritive status, and soil fertility, we investigated to which extent soil parent materials explain nutrient limitations. We found that N limitation was not linked to soil parent materials, but was best explained by climate: ecosystems under harsh (i.e., cold and or dry) climates were more N‐limited than ecosystems under more favourable climates. Contrary to N limitation, P limitation was not driven by climate, but by soil parent materials. The influence of soil parent materials was the result of the tight link between actual P pools of soils and physical–chemical properties (acidity, P richness) of soil parent materials. Some other ground‐related factors (i.e., soil weathering stage, landform) had a noticeable influence on P limitation, but their role appeared to be relatively smaller than that of geology. The relative importance of N limitation versus P limitation was explained by a combination of climate and soil parent material: at global scale, N limitation became prominent with increasing climatic constraints, but this global trend was modulated at lower scales by the effect of parent materials on P limitation, particularly under climates favourable to biological activity. As compared with soil parent materials, atmospheric deposition had only a weak influence on the global distribution of actual nutrient limitation. Our work advances our understanding of the distribution of nutrient limitation at global scale. In particular, it stresses the need to take soil parent materials into account when investigating plant growth response to environment changes.

Constitutive calcium entry and cancer: updated views and insights - Olivier Mignen; Bruno Constantin; Marie Potier-Cartereau; Aubin Penna; Mathieu Gautier; Maxime Guéguinou; Yves Renaudineau; Kenji F. Shoji; Romain Félix; Elsa Bayet; Paul Buscaglia; Marjolaine Debant; et al. (European Biophysics Journal, 2017)

Erratum to: Inhibition of pannexin1 channels alleviates acetaminophen-induced hepatotoxicity - Michaël Maes; Mitchell R. McGill; Tereza Cristina da Silva; Chloé Abels; Margitta Lebofsky; James L. Weemhoff; Taynã Tiburcio; Isabel Veloso Alves Pereira; Joost Willebrords; Sara Crespo Yanguas; Anwar Farhood; Alain Beschin; et al. (Archives of Toxicology, 2017)

Inhibition of pannexin1 channels alleviates acetaminophen-induced hepatotoxicity - Michaël Maes; Mitchell R. McGill; Tereza Cristina da Silva; Chloé Abels; Margitta Lebofsky; James L. Weemhoff; Taynã Tiburcio; Isabel Veloso Alves Pereira; Joost Willebrords; Sara Crespo Yanguas; Anwar Farhood; Alain Beschin; et al. (Archives of Toxicology, 2017)

Connexins, Pannexins, and Their Channels in Fibroproliferative Diseases - Bruno Cogliati; Gregory Mennecier; Joost Willebrords; Tereza Cristina Da Silva; Michaël Maes; Isabel Veloso Alves Pereira; Sara Crespo Yanguas; Francisco Javier Hernandez-Blazquez; Maria Lúcia Zaidan Dagli; Mathieu Vinken (The Journal of Membrane Biology, 2016)

Experimental models of liver fibrosis - Sara Crespo Yanguas; Bruno Cogliati; Joost Willebrords; Michaël Maes; Isabelle Colle; Bert van den Bossche; Claudia Pinto Marques Souza de Oliveira; Wellington Andraus; Venâncio Avancini Alves; Isabelle Leclercq; Mathieu Vinken (Archives of Toxicology, 2016)

First insights into indoor and outdoor Culicoides activity related to the risk period for Bluetongue virus transmission in Eastern Slovakia - Adela Sarvašová; Alica Kočišová; Erika Liptáková; Helena Hiavatá; Bruno Mathieu (Acta Parasitologica, 2016)
The epizootic of Bluetongue virus (BTV) throughout Europe in 2006 revealed insufficient knowledge regarding seasonal activities, endo/exophilic and endo/exophagic behaviour of the species of the

Effect of weaning age and the use of different sized Artemia nauplii as first feed for jade perch Scortum barcoo - Stijn Van Hoestenberghe; Mathieu Wille; Evelien De Swaef; Bruno M. Goddeeris; Nancy Nevejan (Aquaculture International, 2015)

Potential of Opuntia ficus-indica for air pollution biomonitoring: a lead isotopic study - Eliane El Hayek; Antoine El Samrani; Bruno Lartiges; Veronique Kazpard; Mathieu Benoit; Marguerite Munoz (Environmental Science and Pollution Research, 2015)

Phytoextraction from mine spoils: insights from New Caledonia - Guillaume Losfeld; Romain Mathieu; Laurent L’Huillier; Bruno Fogliani; Tanguy Jaffré; Claude Grison (Environmental Science and Pollution Research, 2015)

Tree mineral nutrition is deteriorating in Europe - Mathieu Jonard; Alfred Fürst; Arne Verstraeten; Anne Thimonier; Volkmar Timmermann; Nenad Potočić; Peter Waldner; Sue Benham; Karin Hansen; Päivi Merilä; Quentin Ponette; Ana C de la Cruz; et al. (Global Change Biology, 2015)
The response of forest ecosystems to increased atmospheric CO 2 is constrained by nutrient availability. It is thus crucial to account for nutrient limitation when studying the forest response to climate change. The objectives of this study were to describe the nutritional status of the main European tree species, to identify growth‐limiting nutrients and to assess changes in tree nutrition during the past two decades. We analysed the foliar nutrition data collected during 1992–2009 on the intensive forest monitoring plots of the ICP Forests programme. Of the 22 significant temporal trends that were observed in foliar nutrient concentrations, 20 were decreasing and two were increasing. Some of these trends were alarming, among which the foliar P concentration in F. sylvatica , Q. Petraea and P. sylvestris that significantly deteriorated during 1992–2009. In Q. Petraea and P. sylvestris , the decrease in foliar P concentration was more pronounced on plots with low foliar P status, meaning that trees with latent P deficiency could become deficient in the near future. Increased tree productivity, possibly resulting from high N deposition and from the global increase in atmospheric CO 2 , has led to higher nutrient demand by trees. As the soil nutrient supply was not always sufficient to meet the demands of faster growing trees, this could partly explain the deterioration of tree mineral nutrition. The results suggest that when evaluating forest carbon storage capacity and when planning to reduce CO 2 emissions by increasing use of wood biomass for bioenergy, it is crucial that nutrient limitations for forest growth are considered.

Primary hepatocytes and their cultures in liver apoptosis research - Mathieu Vinken; Michaël Maes; André G. Oliveira; Bruno Cogliati; Pedro E. Marques; Gustavo B. Menezes; Maria Lúcia Zaidan Dagli; Tamara Vanhaecke; Vera Rogiers (Archives of Toxicology, 2014)

Meta-analysis of environmental contamination by phthalates - Alexandre Bergé; Mathieu Cladière; Johnny Gasperi; Annie Coursimault; Bruno Tassin; Régis Moilleron (Environmental Science and Pollution Research, 2013)

Chronic ingestion of cadmium and lead alters the bioavailability of essential and heavy metals, gene expression pathways and genotoxicity in mouse intestine - Jérôme Breton; Kelly Le Clère; Catherine Daniel; Mathieu Sauty; Lauren Nakab; Thierry Chassat; Joëlle Dewulf; Sylvie Penet; Christophe Carnoy; Patrick Thomas; Bruno Pot; Fabrice Nesslany; et al. (Archives of Toxicology, 2013)

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

Viral infection resistance conferred on mice by siRNA transgenesis - Nathalie Daniel-Carlier; Ashraf Sawafta; Bruno Passet; Dominique Thépot; Mathieu Leroux-Coyau; François Lefèvre; Louis-Marie Houdebine; Geneviève Jolivet (Transgenic Research, 2013)

Alkylphenolic compounds and bisphenol A contamination within a heavily urbanized area: case study of Paris - Mathieu Cladière; Johnny Gasperi; Catherine Lorgeoux; Céline Bonhomme; Vincent Rocher; Bruno Tassin (Environmental Science and Pollution Research, 2013)

Proteomic and metabolomic responses to connexin43 silencing in primary hepatocyte cultures - Mathieu Vinken; Michaël Maes; Rachel Cavill; Dirk Valkenborg; James K. Ellis; Elke Decrock; Luc Leybaert; An Staes; Kris Gevaert; André G. Oliveira; Gustavo B. Menezes; Bruno Cogliati; et al. (Archives of Toxicology, 2013)

Meta-analysis of environmental contamination by alkylphenols - Alexandre Bergé; Mathieu Cladière; Johnny Gasperi; Annie Coursimault; Bruno Tassin; Régis Moilleron (Environmental Science and Pollution Research, 2012)

Auswerteverfahren zur Kontrolle der Verfüllqualität in Erdwärmesonden mit faseroptischen Temperaturmessungen - Mathieu Riegger; Philipp Heidinger; Bruno Lorinser; Ingrid Stober (Grundwasser, 2012)

Engineering of a phosphorylatable tag for specific protein binding on zirconium phosphonate based microarrays - Mathieu Cinier; Marc Petit; Frédéric Pecorari; Daniel R. Talham; Bruno Bujoli; Charles Tellier (JBIC Journal of Biological Inorganic Chemistry, 2012)

Proteomic analysis of NME1/NDPK A null mouse liver: evidence for a post-translational regulation of annexin IV and EF-1Bα - Arnaud Bruneel; Dominique Wendum; Valérie Labas; Odile Mulner-Lorillon; Joelle Vinh; Nelly Bosselut; Eric Ballot; Bruno Baudin; Chantal Housset; Sandrine Dabernat; Marie-Lise Lacombe; Mathieu Boissan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

Sawhorse-type diruthenium tetracarbonyl complexes containing porphyrin-derived ligands as highly selective photosensitizers for female reproductive cancer cells - Frédéric Schmitt; Mathieu Auzias; Petr Štěpnička; Yoshihisa Sei; Kentaro Yamaguchi; Georg Süss-Fink; Bruno Therrien; Lucienne Juillerat-Jeanneret (JBIC Journal of Biological Inorganic Chemistry, 2009)

Consequences of prolonged total thermoneutral immersion on muscle performance and EMG activity - Mathieu Coulange; Florence Riera; Bruno Melin; Stephane Delliaux; Nathalie Kipson; Chantal Gimenez; Claude Robinet; Yves Jammes (Pflügers Archiv - European Journal of Physiology, 2008)

Consequences of prolonged total body immersion in cold water on muscle performance and EMG activity - Mathieu Coulange; François Hug; Nathalie Kipson; Claude Robinet; Anne Virginie Desruelle; Bruno Melin; Chantal Jimenez; François Galland; Yves Jammes (Pflügers Archiv - European Journal of Physiology, 2006)